KESEJAJARAN KARAKTER TOKOH DALAM BUKU “ANAK KAMPUNG PALING FENOMENAL” KARYA DR. M. MUFTI MUBAROK - Putra, Agus Darma (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2022)
Character was a person's nature, which refers to a person's personal qualities. The characters in the book “The Most Phenomenal Village Children” are no exception, who have the same characters in this study. The purpose of this study is to find out the form of parallel reality of the characters through the words and behavior of the characters in the book "The Most Phenomenal Village Children" by Dr. M. Mufti Mubarok. While this type of research is qualitative literature research using descriptive methods. The results of the study found several forms of reality of character alignment through the words and behavior of the characters such as: being humble, ambitious, empathetic and caring for others, having a strong character, respecting friends and foes, having stable emotions, being brave, patient, and keeping the spirit up. As for other findings from the alignment of characters, through the same words and behavior is a good attitude, which can be an inspiration and innovation for the community.